Spatially Controlled Surface Deposition of a Versatile ATRP Macroinitiator by Inkjet Printing - Fernandes, Sérgio Miguel Rodrigues (2018)
Functionalization of gold surfaces for possible coating applications with a one-step pattern deposition technique in inkjet printing was achieved by the following methodology: First, the atom transfer radical polymerization (ATRP) macroinitiator, i.e. poly[2-(2-bromoisobutyryloxy) ethyl methacrylate] (PBIEM) was synthesised by the reversible-addition fragmentation transfer (RAFT) polymerization of 2-hydroxyethyl methacrylate (HEMA) and its subsequent functionalization with α-bromoisobutyryl bromide (BIBB), see scheme 5-1 and 5-2. Attenuated total reflectance Fourier transform infrared spectroscopy (ATR FT-IR) and proton nuclear magnetic resonance spectroscopy (1H-NMR) confirmed the successful synthesis of poly(HEMA) (PHEMA) by RAFT, see figure 5-2. From 1H NMR spectra, the number-average molecular weight (Mn) of one prepared precursor was determined to be approximately 23 kDa (6th PHEMA). The functionalization of PHEMA with BIBB was confirmed by ATR FT-IR and 1H-NMR spectroscopy as well, see figure 5-4 and figure 5-5. Secondly, the prepared PBIEM was deposited on gold surface by inkjet printing. Several inks were produced being that the PBIEM (derived from 6th PHEMA 23kDa) 10% (w/w) solution in N, N-Dimethylformamide (DMF) yielded more dense grafting layers. Water contact angle measurements (CA), optical microscopy and infrared microscopy were used to prove the grafting of the ATRP-macroinitiator on gold. The atomic force microscopy (AFM) step height images provided the thickness and roughness and of deposit initiator layers on gold surfaces. The obtained PBIEM layer thickness is approximately ~17 nm. Last, poly(N-isopropylacrylamide) (PNIPAM) side chains were synthesised via grafting from by ATRP to produce bottlebrush type structures. Infrared microscopy and AFM were used to confirm the successful fabrication of bottlebrush polymers. Conversions up to 15% were obtained.